2011
DOI: 10.3109/01443615.2010.546906
|View full text |Cite
|
Sign up to set email alerts
|

The influence of obesity on ICSI outcomes in women with polycystic ovary syndrome

Abstract: The objective of the study was to compare intracytoplasmic sperm injection (ICSI) outcome and gonadotropin doses between obese women with PCOS and non-obese patients with PCOS. This follow-up study represents ICSI outcomes in obese women with PCOS (BMI ≥ 30 kg/m(2)) compared with non-obese women with PCOS (BMI < 30 kg/m(2)). Obese (n = 18) and non-obese (n = 26) women with PCOS underwent long protocol pituitary suppression, ovarian stimulation and ICSI with fresh embryo transfer. Obese patients with PCOS requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
40
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 44 publications
3
40
1
Order By: Relevance
“…Overweight is associated with several symptoms of PCOS including hirsutism, a clinical marker of elevated androgens, higher rates of oligo‐ and amenorrhoea, infertility and miscarriage compared with lean women . We found that AMH and AMHR‐II expression both PCOS and non‐PCOS women was negatively correlated with BMI.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Overweight is associated with several symptoms of PCOS including hirsutism, a clinical marker of elevated androgens, higher rates of oligo‐ and amenorrhoea, infertility and miscarriage compared with lean women . We found that AMH and AMHR‐II expression both PCOS and non‐PCOS women was negatively correlated with BMI.…”
Section: Discussionmentioning
confidence: 64%
“…17 Overweight is associated with several symptoms of PCOS including hirsutism, a clinical marker of elevated androgens, 18 higher rates of oligo-and amenorrhoea, infertility and miscarriage compared with lean women. 19 We found that AMH and AMHR-II expression both PCOS and non-PCOS women was negatively correlated with BMI. The observed inverse association between AMH, AMHR-II expression and BMI suggests that obesity-related hormonal dysfunction of adipose tissue is a factor leading to the reduction in ovarian reserve in both obese PCOS and non-PCOS women.…”
Section: Discussionmentioning
confidence: 66%
“…A cohort analysis on 1417 cycles with 487 patients indicated the number of oocytes retrieved was negatively correlated with BMI increasing and the dose of gonadotropin [14]. While high level of leptin inhibit FSH secretion in obese patients and suppress the secretion of estrogen from theca cells [42], obese PCOS women was found to be associated with reduced number of oocytes retrieved [43][44][45]. However, the relationship between obesity, PCOS and the outcomes of IVF/ICSI remains controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Hirsutism, a clinical marker of elevated androgens, is also more severe in obese PCOS women (45). Obese PCOS patients also have higher rates of oligo-and amenorrhea, infertility, and miscarriage compared with lean women with the disorder (8,45,65). Additionally, between 50 and 70% of women with PCOS suffer from some degree of insulin insensitivity, and SI scores worsen with increasing body mass index (BMI) (21,28,43,62).…”
mentioning
confidence: 99%